On the Improvement of the Legal Regulation in the Field of Atmospheric Air Protection in the Russian Federation - Kseniya S. Eruzalimova (Сибирское юридическое обозрение, 2017)
The article considers the problems of inconsistence in the atmospheric air protection legislation. In particular, the Author indicates the unfounded distinctions in the competence of federal and regional environment protection bodies concerning the right to bring a suit against violators of the air protection rules and regulations. On the basis of extensive research of current legislation and case law the Author suggests optimizing the competence of environment protection bodies.